A cross-sectional survey of COVID-19: attitude and prevention practice among Syrians - Batoul Bakkar; Fatema Mohsen; Humam Armashi; Marah Marrawi; Nizar Aldaher (Heliyon, 2022)
Introduction: Coronavirus disease of 2019 has overwhelmed public health systems worldwide and forced governments to impose draconian lockdowns on entire populations. With no vaccine or treatment during the early days of the pandemic, it is of paramount importance to assess the public’s awareness about COVID-19 so that prevention-focused educational campaigns can be sufficiently deployed. This study aimed to gauge the Syrian public’s adherence to infection control measures by assessing attitudes and practices during the pandemic which ravaged an already war-torn Syria. Methods: The web-based cross-sectional study was conducted in March 2020, nearly 11 years into the Syrian crisis. The survey contained 3 sections: socio-demographic characteristics, attitudes, and practice. Multivariable logistic regression analysis was performed to identify factors associated with good practices and negative attitudes. Data were analyzed using the Statistical Package for Social Sciences version 25.0. Results: Of the 3586 participants, 68.2% were females, 50.8% were unemployed, and 79.2% were college-educated. Only 1402 (39.1%) participants wore face masks when leaving their homes. Multiple logistic regression analysis revealed that female, age, and residence were factors associated with good practices such as avoiding mass gatherings, wearing face masks, and maintaining a 1-meter interpersonal distance. However, age and occupation were factors associated with negative attitudes towards the closure of universities and schools, travel bans, and quarantines for travellers. Conclusion: This survey highlights the need to address specific populations using various measures; there should be a specialized method of prevention for each occupation, age group, and place of residence to contain further outbreaks of COVID-19. This can be achieved through targeted awareness campaigns.